2014
DOI: 10.2310/8000.2013.131131
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance evaluation of a simple linear protocol for the treatment of impending status epilepticus in a pediatric emergency department 2 years postimplementation

Abstract: Objective: To evaluate the efficacy and safety of a simple linear midazolam-based protocol for the management of impending status epilepticus in children up to 18 years of age. Methods: This is a descriptive, quality assessment, retrospective chart review of children presenting with the chief complaint of seizure disorder in the emergency department (ED) of a tertiary care pediatric hospital and a triage category of resuscitation or urgent from April 1, 2009, to August 31, 2011 In children with at least one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…The first phase of each QI initiative consisted of multidisciplinary engagement and careful surveillance of current practice at individual institutions. Observed causes of variation and delays included failure to correctly identify time of seizure onset, inconsistent physician orders, delayed decision making regarding when to administer drugs, lack of standing orders for medication as needed, varying experience of staff and personnel, knowledge gaps, inefficient communication, and issues with availability of antiepileptic medication …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first phase of each QI initiative consisted of multidisciplinary engagement and careful surveillance of current practice at individual institutions. Observed causes of variation and delays included failure to correctly identify time of seizure onset, inconsistent physician orders, delayed decision making regarding when to administer drugs, lack of standing orders for medication as needed, varying experience of staff and personnel, knowledge gaps, inefficient communication, and issues with availability of antiepileptic medication …”
Section: Resultsmentioning
confidence: 99%
“…All three studies chose to standardize treatment by creating or modifying a treatment protocol. Following employment of a linear, single‐agent protocol for pediatric patients presenting with impending status epilepticus, 93% (51 of 55) of seizures were appropriately treated with first‐line midazolam and 86% (6 of 7) were appropriately treated with phenytoin as second‐line therapy (no comparison group available) . In another study that used an automatically activated electronic order set for any pediatric patient with a diagnosis of seizure, the mean time from impending status recognition to first‐line therapy improved (3.74 vs 7.72 minutes; p < 0.0001) as did delay to second‐line therapy (25 vs 49.5 minutes; p < 0.0001) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Automated calculation of the quality measure and time to treatment should facilitate future quality improvement efforts. For pediatric CSE, protocol‐driven initiatives are effective at decreasing time to treatment 18‐22 . One author suggested that hospitals should organize rapid response teams that respond to seizures with similar urgency and coordination to “code teams” for cardiorespiratory arrest 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is unclear on the effectiveness of protocol adherence. A retrospective chart review of children presenting with seizures to the emergency department found that adherence to a protocol successfully treated 55 episodes in 46 patients, 5 although there was no comparison group in the study. Conversely, a prospective study of 54 adults with status epilepticus found that patient outcomes at an academic hospital, which followed a status epilepticus protocol closely, were not different from outcomes at regional hospitals, which often deviated from the status epilepticus protocol.…”
mentioning
confidence: 99%